Phrakru Suchinnanthakit’s Role in Building a Strong Community: a Case Study of Ban Pong Kham Community, Santisuk District, Nan Province - Bhanuwangso , Phramaha Phatthanaphong; Phra Rajanandhawachrabandit; Tawboonyapinikun, Phrapalad Kittisak (Mahachula Academic Journal, 2025)
The purpose of this article was (1) to study the problems and context of Ban Pong Kham community, Santisuk District, Nan Province; (2) to study the process of building a strong community of Ban Pong Kham community, Santisuk District, Nan Province; and (3) to study the role of Phrakhru Suchinanantakit in building a strong community of Ban Pong Kham community, Santisuk District, Nan Province. This research was qualitative, studying data from documents and fieldwork, collecting interview data from 23 key informants, and analyzing data by descriptive content method. The research results found that: The problems of Ban Pong Kham community, Santisuk District, Nan Province, had many aspects as follows: (1) problems of natural resources and environment, (2) problems of occupation, income and community economy, (3) problems of occupation, income and community economy, (4) problems of debt and financial security, (5) problems of infrastructure and public utilities, (6) problems of society, leaders and participation, and (7) problems of social behavior, drugs and youth. The context of Ban Pong Kham community was a small community located amidst beautiful nature, with intricate mountain ranges and unique tranquility. The way of life of most villagers is still connected to nature and self-reliance in the traditional way. The main occupations are agriculture, animal husbandry and farming. Most of the population in the community believe in nature, ancestral spirits and still firmly adhere to Buddhism. The process of building a strong community of Ban Pong Kham community, Santisuk District, Nan Province was the development of Ban Pong Kham community from cooperation between leaders and people, emphasizing building trust, unity and good attitudes towards each other, along with promoting self-reliance through occupations and local wisdom. Phra Khru Sujinanantakit played an important role in the comprehensive development of Ban Pong Kham community by using the temple as a center of learning, organizing training, and creating a new thinking system for sustainability. He was a leader in coordinating cooperation, promoting unity and developing the mental immunity of the community as follows: (1) economics, (2) society, (3) culture and (4) environment.